Targeting the “Sweet Side” of Tumor with Glycan-Binding Molecules Conjugated-Nanoparticles: Implications in Cancer Therapy and Diagnosis - Nora Bloise; Mohammad Okkeh; Elisa Restivo; Cristina Della Pina; Livia Visai (Nanomaterials, 2021)
Nanotechnology is in the spotlight of therapeutic innovation, with numerous advantages for tumor visualization and eradication. The end goal of the therapeutic use of nanoparticles, however, remains distant due to the limitations of nanoparticles to target cancer tissue. The functionalization of nanosystem surfaces with biological ligands is a major strategy for directing the actions of nanomaterials specifically to tumor cells. Cancer formation and metastasis are accompanied by profound alterations in protein glycosylation. Hence, the detection and targeting of aberrant glycans are of great value in cancer diagnosis and therapy. In this review, we provide a brief update on recent progress targeting aberrant glycosylation by functionalizing nanoparticles with glycan-binding molecules (with a special focus on lectins and anti-glycan antibodies) to improve the efficacy of nanoparticles in cancer targeting, diagnosis, and therapy and outline the challenges and limitations in implementing this approach. We envision that the combination of nanotechnological strategies and cancer-associated glycan targeting could remodel the field of cancer diagnosis and therapy, including immunotherapy.